Field report PAC 671: the sustainability of audit firm in delivery high quality work / Ahmad Rashidi Rosli - Rosli, Ahmad Rashidi (Universiti Teknologi MARA, Terengganu, 2024)
Morison LC PLT, a dynamic professional services firm established in 2017 and based in Malaysia, offers a comprehensive suite of accounting and financial services to both local and international clients. The firm has rapidly evolved from a dedicated audit firm to a one-stop shop for all financial needs. They provide a holistic approach to financial well-being, encompassing audits, tax planning, financial management, and advisory services. This full-service approach ensures that clients receive a broad range of expert assistance under one roof, addressing all aspects of their financial operations with precision and care.